2010
DOI: 10.1111/j.1750-2659.2009.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of live attenuated influenza vaccine in children 6 months to 17 years of age

Abstract: Please cite this paper as: Belshe et al. (2010). Efficacy of live attenuated influenza vaccine in children 6 months to 17 years of age. Influenza and Other Respiratory Viruses 4(3), 141–145. Background  It has been suggested that live attenuated influenza vaccine (LAIV) may be less effective in older individuals because of prior wild‐type influenza infections. LAIV is currently approved in the United States, South Korea and Hong Kong for individuals 2–49 years of age. Objective  To examine data from previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
5
32
1
1
Order By: Relevance
“…2b). Age-stratified data from this study were published by Belshe et al [9], showing similar relative efficacy of LAIV vs. TIV in the age groups 6-11 years (31%; 95% CI: −8%-57%; 1376 subjects) and 12-17 years (30%; 95%CI: −43%-66%; 835 subjects), both of which, however, were not statistically significant. Incidences of LRTI were not reported.…”
Section: Children Aged 6-17 Yearssupporting
confidence: 63%
See 2 more Smart Citations
“…2b). Age-stratified data from this study were published by Belshe et al [9], showing similar relative efficacy of LAIV vs. TIV in the age groups 6-11 years (31%; 95% CI: −8%-57%; 1376 subjects) and 12-17 years (30%; 95%CI: −43%-66%; 835 subjects), both of which, however, were not statistically significant. Incidences of LRTI were not reported.…”
Section: Children Aged 6-17 Yearssupporting
confidence: 63%
“…An important question STIKO sought to answer is up to what age LAIV confers better protection against influenza than TIV. In adults, several studies have shown that LAIV provides worse protection than TIV against laboratory-confirmed influenza (see meta-analysis by Belshe et al [9]). This was also observed in a randomized study comparing LAIV, TIV, and placebo in very young adults with a mean age of 23.3 years (range 18-49 years) [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst studies do support the notion that viral shedding and immune response to LAIV may decline upon repeated use 47,48 and with increasing age, 49 this has not yet been correlated to a reduction in vaccine efficacy. 50 Moreover, use of live vaccine on an annual basis is unique to influenza and further study is required to understand the implications. For example, whether subtle changes in antigenicity affect LAIV "take" more than IIV, requiring more frequent strain updates or different methods of strain selection than that established for IIV.…”
Section: (Ii)prior Vaccination and Immunitymentioning
confidence: 99%
“…Since then, two lineages (Victoria, named after B/Victoria/2/1987, and Yamagata, named after B/Yamagata/16/ 1988) can be distinguished genetically and antigenically on the basis of their HA (1,3,4). Until 2000, one of these two lineages tended to dominate each season; however, since 2001 both influenza B virus lineages have been cocirculating in human populations each year (5,6).…”
mentioning
confidence: 99%